The Representation of History in Digital Media and Its Influence on Collective Memory - Ramadhan, Fahri; Setiawan, Bayu; Maulana, Fajar (Journal Social Humanity Perspective, 2024)
This paper discusses the effect that the representation of history in digital media has on collective memory with a particular emphasis on its consequences in the sphere of management. In the digital era, history is no longer limited to a textbook, all the archives or institutional accounts; it is being spread globally by the social media and video-sharing sites as well as web communities, where the history is reinterpreted, challenged, and co-created. This study employs the use of a qualitative methodology to research various participants based on their interviews to examine the way audiences interact with digital historical material, how they engage in negotiating meaning, and how the interactions influence the overall formation of common sense about the past. These results indicate that digital media will render history more convenient and personal to experience, especially among younger viewers, yet may also lead to the dissection or watering down of narratives. The interpretations of the audience are also influenced by the active involvement of online dialogue, which gives rise to collective memory due to the interaction, debate, and exchange of other views. Notably, the research indicates that the digital media strengthens national identity and at the same time creates space on which the challenged and plural memory can emerge to challenge institutional authority. On the managerial side, the implications of these dynamics are significant: historical narratives can be seen as strategic assets that can be used to affect the organizational legitimacy, identity construction and accountability. Organizations are no longer able to use one direction storytelling but need to dialogically interact with the various accounts of the past to continue to maintain trust and relevance. Finally, the study will help in understanding further the complexity of digital media, history and collective memory entanglement and provide information on how managers and institutions can negotiate across this shifting landscape in a responsible and strategic way.